1969
DOI: 10.1007/bf00683849
|View full text |Cite
|
Sign up to set email alerts
|

Lactones of the fruit ofXanthogalum purpurascens

Abstract: with literature data, and also taking into account the fact that all the quinones known for sage are phenanthrene derivatives, we have established that the quinone isolated from the roots of Salvia nemorosa L. is 7-acetoxyroyleanone, which has been obtained previously [2] from the roots of Inula royleana together with royleanone and 6, 7-dehydroroyleanone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Sesquiterpene hydrocarbons were present at 25.78%, the most important of which are aromadendrenedehydro (4.64%), β-elemene (4.56%), and germacrene-D (4.47%), respectively. In a previous study, the chemical composition of A. purpurascens fruits was reported to be rich in isooxypucledanin, coumarin (agacillin), and β-sitosterol [30,55]. Acyl-and pyranocoumarins were observed in the ethanol extracts of root and rhizomes [56].…”
Section: Gc−ms Analyses Of Essential Oil Of a Purpurascens Rootmentioning
confidence: 99%
See 1 more Smart Citation
“…Sesquiterpene hydrocarbons were present at 25.78%, the most important of which are aromadendrenedehydro (4.64%), β-elemene (4.56%), and germacrene-D (4.47%), respectively. In a previous study, the chemical composition of A. purpurascens fruits was reported to be rich in isooxypucledanin, coumarin (agacillin), and β-sitosterol [30,55]. Acyl-and pyranocoumarins were observed in the ethanol extracts of root and rhizomes [56].…”
Section: Gc−ms Analyses Of Essential Oil Of a Purpurascens Rootmentioning
confidence: 99%
“…The chemical diversity in the underground and aboveground parts of the plant is so different that the essential oil components of the plant can significantly vary [23]. In previous studies, sterols such as xanthogonine, xanthogalol acetate, xanthogalol, xanthalin, ostruthol, isooxyposedan, β-sitosterol, coumarin, agacillin, and acyl-and pyranocoumarins were found in different plant tissues of Angelica species [30][31][32].…”
mentioning
confidence: 99%
“…Xanthogalum purpurascens fruits have been previously reported as rich in coumarin (agasyllin), isooxypeucedanin and β-sitosterol (2)(3)(4). Acyl-and pyranocoumarins were identifi ed in the ethanol extracts of root and rhizomes (5,6).…”
Section: Introductionmentioning
confidence: 98%
“…Prior biochemical researches on Angelica sp. has indicated in plant tissue sterols such as ostruthol, xanthogalin, xanthalin, xanthogalol, xanthogalol acetate, agasyllin, isooxypeucedanin and β-sitosterol and coumarins (Sokolova and Nikonov, 1969, Ozek et al, 2006). It was reported that acyl- and pyrano coumarins were defined in the root and rhizomes ethanol extracts and also, A. purpurascens essential oil had antimicrobial activity (Mahboubeh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%